Carotid plaque score and ischemic stroke risk stratification through a combination of B-mode and contrast-enhanced ultrasound in patients with low and intermediate carotid stenosis - Li, Fang; Gu, Shi-Yao; Zhang, Lu-Ni; Chen, Jing; Yao, Ming-Hua; Wu, Ting-Ting; Ma, Ji; Jia, Cai-Xia; Wu, Rong (Frontiers in Cardiovascular Medicine, 2023)
Objective: The occurrence of ischemic stroke is closely related to the characteristics of carotid plaque. Due to the effect of stroke risk stratification based on B-mode ultrasound and CEUS has not been studied in patients with low and intermediate carotid stenosis, we construct and validate a carotid plaque score and ischemic stroke risk stratification using a combination of B-mode and contrast-enhanced ultrasound, so as to provide new convenient strategies to stratify these patients for preventing stroke. Methods: This retrospective study evaluated 705 patients with low and intermediate carotid stenosis who underwent B-mode and contrast enhanced ultrasound (CEUS) from November 2021 to April 2023. Qualitative B-mode and CEUS features of carotid plaques were analyzed with univariable and multivariable logistic regression to construct a carotid plaque (CP) score. Then we combined the CP score with Essen Stroke Risk Score (ESRS) to develop ischemic stroke risk stratification(ISRS). Results: A total of 705 patients with low and intermediate carotid stenosis in 394 symptomatic patients (mean age 71.03 ± 10.48) and 311 asymptomatic patients (mean age 65.13 ± 10.31) were included. Plaque echogenicity, plaque morphology, carotid intima-media thickness (C-IMT) in B-mode ultrasound and intraplaque neovascularization (IPN) grading and Perfusion pattern in CEUS were significantly associated with Ischemic stroke. The ISRS incorporating these five predictors and ESRS showed good discrimination and calibration in both the primary cohort (area under the curve, 0.91; Hosmer-Lemeshow test, p =0.903 and the validation cohort (area under the curve, 0.84; Hosmer-Lemeshow test, p = 0.886). Conclusion: We developed an effective and practical tool to identify and stratify patients with low and intermediate carotid stenosis, based on a CP score and ISRS estimation. Our study may provide a new insights into managing patients without no indication of surgery.